The Impact of Diversification and Ownership Structure on the Performance of Vietnamese Banks - Bui Kim, Yen; Tran Trieu Anh, Khoa; Huynh Thanh, Binh; Truong Nguyen Kieu , Phuong; Nguyen Khoa Trieu, Son (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
In the backdrop of a thriving financial market in Vietnam, income diversification emerges as a topic of keen interest and considerable debate. Under the influence of ownership structure, diversification may yield positive outcomes. This study evaluates the impact of diversification and ownership structure on bank performance, drawing from data of 27 listed banks in Vietnam spanning from 2010 to 2023. Employing a combination of FEM with robust standard error, FGLS and two-step system GMM methods to address model deficiencies. Research findings indicate that diversification positively impacts operational efficiency, but under the influence of State ownership exceeding 20%, it yields adverse effects. Through this study, commercial banks and the Vietnamese Government can adjust diversification and ownership structure to maximize profits.